Immigration and emigration in Colonia Caesar Augusta (1st-2nd century AD) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The objective of this paper is to study the dynamics of mobility among the inhabitants of Caesar Augusta. The basis of the study is constituted by the epigraphic documentation related to this colony. The analysis of the different types of mobility and of the causes that motivated the displacements are the main axes of this contribution.
Keywords: Immigration; Emigration; Mobility; Caesar Augusta; Latin Epigraphy